(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Due to its excellent morphological resolution and capacity to image a variety of structures, including bones, lungs, abdominal viscera, and pelvic organs, CT is recommended in many abdominal disorders. Aim of the work: The aim of this study is to highlight the accuracy of multi-detector computed tomography scan in diagnosing the different fatty lesions of the renal and adrenal regions by comparing the CT study of the benign lesions with their follow up CT scan and comparing the CT study of the malignant cases with their histo-pathological results. Patients and Methods: The current study included 34 patients referred to Radiology department, Theodor Bilharz Research Institute. Their age ranged from 20 years to 81 years old with average (56.35 years±13.61). Most of the patients were males 21cases while female were 13 cases. The patients were referred from general surgery and urology departments of Theodor Bilharz Research Institute hospital as well as the outpatient clinics to perform MDCT in the period from November 2021 to June 2022. Results: MDCT examinations were done for 34 patients and concluded that MDCT should be used in the first place in the course of diagnostic procedures of patients with renal and adrenal region fatty lesions and this was justified by an overall diagnostic accuracy of 100% for benign lesions and 82% for malignant lesions, where MDCT could correctly diagnose (33/34) cases and only 1 case was misdiagnosed, confirming the ability of MDCT to show up the accurate diagnosis, the exact location, extent of tumor, along with involvement of adjacent organs and vessels. Conclusion: It also has a high accuracy in differentiation of malignant from benign lesions and detection of lymph node involvement & metastasis. There by improving the prognosis.